A comparison of child development, growth and illness in home-care and day-care center settings. Issue 6 (6th May 2020) - Limtrakul, Darunnee; Ongprasert, Krongporn; Ayood, Pisittawoot; Sapbamrer, Ratana; Siviroj, Penprapa
Abstract : Purpose: Childcare is an essential part of early life environment that has a significant influence on lifelong physical and mental health. This study aimed to examine the relationship between development, growth and frequency of illness in different types of care. Design/methodology/approach: This cross-sectional study recruited 177 children aged 30–36 months and their caregivers. Of these 66 were being cared for at home and 111 were attending out-of-home day-care facilities. An interview form, growth measurement and the Denver Developmental Screening Test II were collected. The association between child developmental, growth and illness variables was analyzed with Chi-square, Fisher's exact and Mann–Whitney U tests. Findings: This study found that the development and growth results did not show statistically significant differences between the home-care and day-care groups. The number of minor illnesses was significantly lower in home-care children than in day-care children (OR = 0.33, 95% CI = 0.15-0.72). Research limitations/implications: This study indicated that the risk of infection is increased in the children attending day care. Provision of a healthy and safe childcare environment needs to be an essential health promotion strategy to improve family and child well-being. Originality/value: As the number of women's participation in the labor market has increased rapidly over the past decades, so did the number of children in nonparental care. The study findings reflect that the development of a day-care center for children was unclear, whereas the risk of infection was increased. Therefore, provision of a healthy and safe childcare environment needs to be an essential health promotion strategy to improve family and child well-being.